Identifying the Rules of Transition from AD to Dementia and MCI Using Machine Learning - Harsimran Guram, Ashok Sharma (International Journal of Control and Automation, 2020)
Dementia is a broader term which is further divided into neurodegenerative and non-neurodegenerative disease. Neurodegenerative disease is irreversible disease which includes Alzheimer’s disease, Lewy body dementia, Parkinson’s disease, Frontotemporal degeneration etc. With the advent of new technologies and researches in the field of acute diseases, the longevity of human life has increased. But chronic diseases such as dementia has affected the humans neurologically. Dementia is a neurological disease which is accelerating in nature that effects human behavior, speech, thinking ability, mobility etc and leads to imbalance in daily functioning. Various approaches have been employed to identify the cause of this neurological disease. In this paper, we have used dataset of 180 Subjects from 0-36 Months and after applying data preprocessing, Decision Tree based model has been obtained to understand the rules of transition.